Relationship between plasma osmolality and neutrophil/lymphocyte ratio in heart failure with reduced ejection fraction (Annals of Medical Research, 2022)
Aim: Heart failure (HF), a progressive disease, is accompanied by chronic inflammation and changes in osmolality. The neutrophil-to-lymphocyte ratio (NLR) demonstrates a systemic inflammatory response in most diseases; however, the relationship between plasma osmolality and the systemic inflammatory response in HF patients is not yet clear. Therefore, we aimed to investigate the possible associations of NLR with plasma osmolality levels in patients with HF.Materials and Methods: The present study included 189 consecutive patients with chronic HF with an ejection fraction (EF) of